Effect of virtual reality exercise on interventions for patients with Alzheimer’s disease: A systematic review - Yi, Yali; Hu, Yuanyan; Cui, Mengxin; Wang, Cheng; Wang, Jibing (Frontiers in Psychiatry, 2022)
Virtual reality (VR) interventions are increasingly being used in rehabilitating and treating patients with neurological disorders. This study aimed to explore the effects of VR exercise interventions on patients with Alzheimer's disease (AD). A systematic review of the published literature on randomized controlled trials of VR technology applied to patients with AD was conducted using the preferred reporting entry for systematic reviews and Meta-analysis guidelines. Eight studies were included, including a pooled sample of 362 patients with AD. Most studies focused on patients' cognitive and physical functions. VR interventions can help improve cognitive and physical balance in patients with AD.